A regional site response analysis of the Petobo area after the 2018.09.28 Palu–Donggala Indonesia earthquake using an equivalent-linear model - Rini Kusumawardani; Muhsiung Chang; Togani Cahyadi Upomo; Fernando Lopez-Caballero; Dadang Permana (Geoenvironmental Disasters)
Abstract This paper presents a site-specific seismic ground response evaluation through convolution–deconvolution analysis in the Balaroa–Petobo area during the 2018 Palu–Donggala Indonesia earthquake. The equivalent-linear ground response analysis for the earthquake time history recorded at Balaroa was carried out using DEEPSOIL software. The results of the analysis indicate that the EW component of the earthquake motion was amplified more severely (amax) than was the NS component, as it propagated to the Petobo surface. The amplification of the bedrock motion on the Petobo surface was more serious than that on the Balaroa surface, which appears to be due to the differences in the subsurface stratification and material properties of the two sites. The Fourier spectrum and response spectra also showed greater maximum spectral accelerations (Sa,max) and maximum Fourier amplitudes (Af) at the Petobo site than at the Balaroa site. The frequency of surface soil both the Petobo and Balaroa sites computed by using comparison between response spectra analysis and the local modes analysis VS/4*H was indicated the potential decline of surface soil stiffness at Petobo area appear to account for the structural damage and liquefaction flow slides during the 2018 incident.